GAMIFICATION AND STUDENT MOTIVATION IN EFL CLASSROOM - Madoyan, Lusine (Foreign Languages for Special Purposes, 2024)
In today’s educational landscape, the quest to enhance student engagement and motivation remains a paramount concern for educators, particularly in English as a Foreign Language (EFL) classrooms. This article delves into the realm of gamification as a novel approach to address these challenges. It aims to explore the motivational effects of gamified learning experiences in high school and higher education settings, in view of their needs and profiles as well as the potential risks involved. Drawing on insights from experts and research findings, the article explores the concept of gamification and its potential to revolutionize learning experiences in EFL contexts. It examines the core principles of playful learning experiences, the essence of gamification, and its application in fostering student engagement. Through an analysis of design elements, advantages, and challenges, the article offers a comprehensive overview of gamification’s implications for language education. Moreover, it discusses considerations for its effective implementation to enhance student motivation and learning outcomes in EFL classrooms.
Keywords: gamification; student motivation; extrinsic motivation; intrinsic motivation; EFL